Introduction: Ethnographies of power and the powerful. (September 2021) - Archer, Matthew; Souleles, Daniel
This introduction suggests that anthropology often assumes that the people anthropologists work with are relatively powerless. Due to this default, anthropologists tend to design their research and theorizing to reflect a relatively powerless other. We suggest that the accumulated scholarship on studying up, that is, studying those who structure the lives of many others, offers more accurate ways to theorize power and its exercise as partial and situated, as well as more plural and productive ways to imagine anthropological practice and ethics. We also suggest that this line of thinking gives us some ground to speak to the larger direction of the discipline.